Effect of Mycorrhiza and Rhyzobium on Micronutrient Uptake by Soybean at Different Phosphorus Levels in Limed Soil - Khdher, Adel K.; Fattah, Omar A. (Science Journal of University of Zakho, 2013)
A greenhouse pot experiment was conducted to study the effect of inoculation with arbuscular mycorrhiza fungi (AMF) and Bradyrhizobium japonicum at different P levels on mycorrhiza effectiveness Zn, Mn, Cu and Fe contents in soybean plants in limed soil. When the acidic soil was limed, the best phosphorus level for mycorrhizal effectiveness was a medium level 0.02 mg p L-1. The AMF inoculation significantly increased the effectiveness of mycorrhiza as a function of time between 21 to 45 days after planting .The maximum P value found in plants was 5.55 µg p leaf disk-1 at 33 days after planting, while the lowest value (2.94 µg p leafdisk-1 was recorded at 15 days after planting.Co-inoculation soils with AMF and R. japonicum significantly affected the shoot Zn, Mn, Cu and Fe contents with increasing applied phosphorus. The maximum values recorded for shoot Zn, Mn, Cu and Fe was 38.33, 56.0, 9.33 and 175.0 µg g-1 respectively and for AMF inoculation was 77.50 , 46.00 , 12.17 and 151.00 µg g-1 while for Rhizobium inoculation was 46.33, 59.83, 8.67 and 183.83 µg g-1 and for non inoculated 73.83, 42.67, 10.83 and 81.50 µg g-1.